2012
DOI: 10.1016/j.atmosenv.2012.05.030
|View full text |Cite
|
Sign up to set email alerts
|

The atmospheric lifetime of black carbon

Abstract: Atmospheric Environment, 59. 256-263. 10.1016Environment, 59. 256-263. 10. /j.atmosenv.2012 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.Atmospheric Environment (2012) AbstractBlack carbon (BC) in the atmosphere contributes to the human health effects of particulate matter and contributes to radiative forcing of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 44 publications
(43 reference statements)
12
77
0
1
Order By: Relevance
“…For instance, estimating the lifetime by dividing the aerosol burden with its emission rate -a common definition of lifetime used by global aerosol modelers -results in a BC lifetime of 9 days. This is quite comparable to lifetime values reported for BC in the literature, though perhaps still somewhat longer than in most models (Samset et al, 2014;Cape et al, 2012;Ogren and Charlson, 1983).…”
Section: Discussionsupporting
confidence: 77%
“…For instance, estimating the lifetime by dividing the aerosol burden with its emission rate -a common definition of lifetime used by global aerosol modelers -results in a BC lifetime of 9 days. This is quite comparable to lifetime values reported for BC in the literature, though perhaps still somewhat longer than in most models (Samset et al, 2014;Cape et al, 2012;Ogren and Charlson, 1983).…”
Section: Discussionsupporting
confidence: 77%
“…The hydrophilic state of BC affects cloud scavenging and wet deposition, which remains the greatest source of uncertainty in models Vignati et al, 2010b). As a result, the lifetime of BC has been estimated to range from a few days up to 2 weeks (Cape et al, 2012;Ramanathan and Carmichael, 2008). Koch et al (2009) have investigated the performance of a model ensemble (AeroCom) in predicting atmospheric BC concentrations and concluded that the simulations tend to underpredict BC concentrations only in some outflow regions, especially in Asia, but overestimate the concentrations in remote areas, especially at high altitudes.…”
Section: Light-absorbing Carbonmentioning
confidence: 99%
“…Both PM 2.5 and BC have been classified as mesoscale air pollutants that can travel tens to hundreds of kilometers (Krudysz et al, 2008;Wang et al, 2011). This is because their atmospheric lifetime is fairly long so that they can be transported and dispersed within a large region (Cape et al, 2012;Chen et al, 2013). When the atmospheric conditions are stagnant, PM 2.5 and BC concentrations may also increase if local emission sources such as traffic exist.…”
Section: Ufp Pm 25 and Bc Concentrationsmentioning
confidence: 99%